A systematic review of perceived barriers and motivators to physical activity after stroke. Issue 5 (13th September 2012) - Nicholson, Sarah; Sniehotta, Falko F.; van, Frederike; Greig, Carolyn A.; Johnston, Marie; McMurdo, Marion E. T.; Dennis, Martin; Mead, Gillian E
<x xml:space="preserve">Abstract</x> Background and purpose Physical fitness is impaired after stroke, may contribute to disability, yet is amenable to improvement through regular physical activity. To facilitate uptake and maintenance of physical activity, it is essential to understand stroke survivors' perceived barriers and motivators. Therefore, we undertook a systematic review of perceived barriers and motivators to physical activity after stroke. Methods Electronic searches of EMBASE, Medline, CINAHL, and PsychInfo were performed. We included peer‐reviewed journal articles, in English, between 1 January 1966 and 30 August 2010 reporting stroke survivors' perceived barriers and motivators to physical activity. Results Searches identified 73 807 citations of which 57 full articles were retrieved. Six articles were included, providing data on 174 stroke survivors (range 10 to 83 per article). Two reported barriers and motivators, two reported only motivators, and two reported only barriers. Five were qualitative articles and one was quantitative. The most commonly reported barriers were lack of motivation, environmental factors (e.g. transport), health concerns, and stroke impairments. The most commonly reported motivators were social support and the need to be able to perform daily tasks. Conclusion This review has furthered our understanding of the perceived barriers and motivators to physical activity after a stroke. This review will enable the development of tailored interventions to target barriers, while building upon perceived motivators to increase and maintain stroke survivors' physical activity.